PENGARUH BOARD INDEPENDENT TERHADAP VALUE RELEVANCE DENGAN INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Nathania Ayu Nugroho; Saarce Elsye Hatane (Business Accounting Review, 2017)
The objective of this research was to understand the direct affect of board independent towards value relevance. Moreover, this research also aimed to know the indirect affect of board independent towards value relevance with intellectual capital disclosure as mediating variable. This research used 72 manufacturing companies listed in Indonesia Stock Exchange (BEI) during the period of 2010-2015 as the samples. The data analyzed by using WarpPLS version 5.0 software.This research found that board independent affected positively towards intellectual capital disclosure, board independent affected positively towards value relevance, and intellectual capital disclosure affected positively towards value relavance. Furthermore, this research also found that intellectual capital disclosure fails to mediate the influence of board independent towards value relevance.